Heavyweight quantification as restricted quantification - Bács, Gábor (Acta Scientiarum Socialium, 2011)
There is a shared dogma among contemporary metaontologists that heavyweight quantification is unrestricted quantification. In this paper I present an exclusion argument for heavyweight ontological realism and outline a new concepction of lightweight and heavyweight quantification based on the rejection of this dogma.